Comparative Analysis of the Notes on the Accounts Of Information-Technology Servicing Companies in Hungary - Fenyves, Veronika; Bács, Zoltán; Zéman, Zoltán; Böcskei, Elvira; Tarnóczi, Tibor (International Journal of Engineering and Management Sciences, 2018)
In the globalized and accelerated world of our time, challenges can only be met by companies that possess the necessary information and are able to convert it rapidly into organizational knowledge. Annual accounting statements are an important source of information within business relations among companies. The necessary information can only be obtained from the two fundamental parts of the annual statements (balance sheet and profit and loss account) if the notes on the account contains the information that contribute to the more comprehensive interpretation of the other parts of the annual statement. Decision-making based on inadequate knowledge further increases economic risks that are already high. In our research, we examine whether the notes on the accounts of companies include the information, which could help obtain necessary financial knowledge concerning the partner companies. For the analyses, we used the notes on the accounts of companies, which have information-technology services (Hungarian NACE No. 62) as their main line of business. By means of text mining, we analyse the extent to which the notes on the accounts are in conformity with the Accounting Act.